The evasion of Section 187(1)(c) of the Labour Relations Act: National Union of Metalworkers of South Africa v Aveng Trident Steel (a division of Aveng Africa Proprietary Ltd) (JA25/18) [2019] ZALAC 36; (2019) 40 ILJ 2024 (LAC); [2019] 9 BLLR 899 (LAC) - Keith-Bandath, Rasheed (Obiter, 2020)
Section 187(1)(c) of the Labour Relations Act 66 of 1995 (LRA), has over the years proven to be a controversial section. At the heart of the controversy is the question as to whether an employer may terminate employees’ contracts of employment based on operational requirements in circumstances where they refuse to accept changes to terms and conditions of employment. This question came before the courts on a number of occasions and answered in the affirmative by the Labour Appeal Court in Fry’s Metals (Pty) Ltd v National Union of Metalworkers of SA ((2003) 21 ILJ 133 (LAC)), and confirmed on appeal by the Supreme Court of Appeal in National Union of Metalworkers of SA v Fry’s Metals (Pty) Ltd (2005 (5) SA 433 (SCA)). However, the LRA has since been amended with the Labour Relations Amendment Act 6 of 2014 (LRAA). Whether an employer may, in light of the amendments, adopt this approach, was recently considered by the Labour Appeal Court in National Union of Metalworkers of South Africa v Aveng Trident Steel (a division of Aveng Africa Proprietary Ltd) ((JA25/18) [2019] ZALAC 36; (2019) 40 ILJ 2024 (LAC); [2019] 9 BLLR 899 (LAC) (13 June 2019) (Aveng case (LAC)). The judgment is noteworthy as it is the first time that the Labour Appeal Court (LAC) delivered judgment relating to section 187(1)(c) of the LRA post-amendment, thus providing a degree of judicial certainty on the interpretation to be accorded to the amended section.